2010
DOI: 10.1007/s10565-010-9157-3
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyltin activates MAP kinases in human natural killer cells, in vitro

Abstract: Previous studies have shown that dibutyltin (DBT) interferes with the function of human natural killer (NK) cells, diminishing their capacity to destroy tumor cells, in vitro. DBT is a widespread environmental contaminant and has been found in human blood. As NK cells are our primary immune defense against tumor cells, it is important to understand the mechanism by which DBT interferes with their function. The current study examines the effects of DBT exposures on key enzymes in the signaling pathway that regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…The effects of the compounds on MAPK phosphorylation were no longer consistently measurable after 1h. This too is consistent previous studies (Trotta et al, 1998; Aluoch and Whalen, 2005; Aluoch et al, 2006; Odman-Ghazi et al, 2010; Taylor and Whalen, 2011). Longer term consequences of this early activation would result in a number of cellular changes, which could include the types of effects on lytic function and protein expression that were described in previous studies (Hinkson and Whalen, 2009; Hinkson and Whalen, 2010; Kibakaya et al, 2009; Hurd and Whalen, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effects of the compounds on MAPK phosphorylation were no longer consistently measurable after 1h. This too is consistent previous studies (Trotta et al, 1998; Aluoch and Whalen, 2005; Aluoch et al, 2006; Odman-Ghazi et al, 2010; Taylor and Whalen, 2011). Longer term consequences of this early activation would result in a number of cellular changes, which could include the types of effects on lytic function and protein expression that were described in previous studies (Hinkson and Whalen, 2009; Hinkson and Whalen, 2010; Kibakaya et al, 2009; Hurd and Whalen, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Longer incubations of 1 h and 6 h were also carried out to examine the length of any consistent activation of p44/42. The choice of exposure conditions was based on past studies including those where we examined the effect of other compounds known to inhibit NK lytic function on MAPK activation (Trotta et al, 1998; Aluoch and Whalen, 2005; Aluoch et al, 2006; Odman-Ghazi et al, 2010; Taylor and Whalen, 2011.) Those studies showed that the environmental contaminants tributyltin (TBT), dibutyltin (DBT), and ziram inhibit NK lytic function and cell surface-protein expression while altering the activation state of MAPK pathway components (Aluoch and Whalen, 2005; Aluoch et al, 2006; Odman-Ghazi et al, 2010; Taylor and Whalen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition of NK lytic function may be due to their ability to induce activation/phosphorylation of MAPKs and MAP2Ks (Cato et al, 2014). Other environmental contaminants such as tributyltin (TBT) and dibutyltin (DBT) (Kimbrough, 1976) that decrease NK lytic function (Dudimah et al, 2007a,b), while activating the MAPK pathway (Aluoch et al, 2006; Odman- Ghazi et al, 2010), have been shown to alter IFNγ secretion from human immune cells (Lawrence et al, 2015). Thus, it is crucial to determine whether HBCD and TBBPA are also able to alter the secretion of IFNγ from human immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggest that in vitro DBT exposure to natural killer cells activated the MAPK, while it did not showed any effect to protein tyrosine kinase [69]. In addition,…”
Section: Dibutyltin Compounds (Dbt)mentioning
confidence: 95%
“…Subunit of ion channel is the target of ATPase inhibition by means of organotin compounds [68]. Another report suggest that DBT treatment with natural killer cells increased the activation of MAPK, could decrease the function of natural killer cells, while it did not showed any effect to protein tyrosine kinase [69]. TBT treatment to immature male mice has reduced the serum testosterone concentration , downregulated the expression of various enzymes for cholesterol side chain cleavage enzyme P450, 17α-hydoxylase, 3βhydroxysteroid dehydrogenase and 17β hydroxysteroid dehydrogenase.…”
Section: Interference Of Organotin Compounds With Enzymesmentioning
confidence: 99%